Entrepreneurship Education Inside the Japanese Biosphere Reserve to Trigger Work Opportunities for Youth - Mammadova, Aida (European Journal of Sustainable Development, 2021)
Entrepreneurship education is defined as the process of providing students with an enhanced capacity to create the ideas and the skills which will be applicable for the future career. From 2018-2019, for four semesters, we have created the regional activities to create the capacity building training program for the exchange students, inside the UNESCO Mount Hakusan Biosphere Reserve (BR) of Japan. Our purpose was to encourage the students to create their own “eco-business projects”, and not to search for the jobs provided from the outside. More than 140 students have attended the course, which was divided into volunteering practices, homestay activities and hands-on practices. After the course completion more than 86% of the students have indicated the willingness to create their own business and some of the students after course completion started their small businesses and worked as freelancers. BR provided the unique platform to conduct the entrepreneurship education, and interacting with local villagers helped the students to re-evaluate the values needed for the sustainable development.